Safety and effectiveness of fecal microbiota, live-jslm (REBYOTA) administered by colonoscopy for prevention of recurrent infection: 8-week results from CDI-SCOPE, a single-arm, phase IIIb trial - Sahil Khanna; David Yoho; Daniel Van Handel; Brian J. Clark; Tahany Awad; Beth Guthmueller; Daniel Armandi; Whitfield Knapple; Nasia Safdar; Brian Baggott; Karen Simon; Paul Feuerstadt (Therapeutic Advances in Gastroenterology)
Background: Recurrent Clostridioides difficile infection (rCDI) occurs in up to 35% of patients with CDI, and further recurrence is common. Fecal microbiota, live-jslm (RBL) is safe and effective for preventing rCDI in adults following antibiotic treatment for rCDI when administered rectally. There is clinical interest in alternative routes of administration. Objectives: CDI-SCOPE assessed the safety and clinical effectiveness of RBL when administered via colonoscopy to adults with rCDI. Design: Single-arm, exploratory phase IIIb trial conducted at 12 sites in the United States. Methods: Eligible adults with rCDI received one administration of RBL consisting of one 150-mL dose of RBL, delivered via colonoscopy to the right side of the colon. The primary endpoint assessed RBL-related treatment-emergent adverse events (TEAEs) within 8 weeks of RBL administration or until confirmed treatment failure. Secondary endpoints included treatment success (absence of CDI recurrence for 8 weeks following RBL administration), physician experience administering RBL via colonoscopy, and physician perception of participant benefit. Results: Of 54 participants screened, 41 were enrolled and received RBL via colonoscopy; 39 participants completed the 8-week visit. Five TEAEs in four participants (9.8%) were assessed as related to RBL, all of which were gastrointestinal and mild in severity. Overall, 18 participants (43.9%) experienced 33 TEAEs within 8 weeks, most of which were of mild (25/33; 75.8%) or moderate (5/33; 15.2%) severity. No TEAEs led to intensive care unit admission or death. Overall, 39 participants (95.1%) experienced treatment success; 2 participants (4.9%) withdrew consent and had an indeterminate outcome. Among physicians, 90.2% of investigators indicated a “positive” or “very positive” experience administering RBL by colonoscopy. All physicians assessed participant benefit as “much” or “very much” improved. Conclusion: This single-arm study suggests RBL administered via colonoscopy is practical, safe, and effective for preventing CDI recurrence following antibiotic treatment in adults. Trial registration: ClinicalTrials.gov: NCT05831189.